First results from cross-section measurements of α-capture reactions on 93Nb and 96Mo relevant to nuclear astrophysics - Peoviti, Maria; Axiotis, Michail; Foteinou, Varvara; Patronis, Nikolaos; Maragkos, Fotios; Harissopulos, Sotirios; Dimitriou, Paraskevi (HNPS Advances in Nuclear Physics, 2025)
The present work reports on preliminary cross-section results of the 93Nb(α,γ)97Tc and 96Mo(α,γ)100Ru reactions at energies between 6 and 7 MeV, a range relevant to p-process nucleosynthesis. The measurements were conducted at the RUBION Dynamitron Tandem Laboratory of the Ruhr-University Bochum, Germany, using the 4π γ-summing method, utilizing the high efficiency of a 12”×12” NaI(Tl) scintillator.